Female Fandom in The Digital Era: ‘Alternative Universe’ for Promoting Thai Boys Love Drama - Yuliarti, Monika Sri (UI Scholars Hub, 2024)
Digital era has changed human’s life, including in the practice of fandom. It results in a much broader dissemination of fans-related products produced by the fans, such as alternative universe (AU) as part of fan fiction. In addition, nowadays, Thailand popular culture is rising, especially with the boys’ love drama series (Thai BL drama) which caught foreign viewers’ interest, including Indonesians. This study explores how AU can be considered as a tool for promoting Thai BL drama which goes to fandom actively involvement in the promotion of a foreign country's cultural product with taboo value. It is a qualitative content analysis of online texts which focuses on three female AU author accounts on X with more than 5,000 followers. It is found that AU does not directly impact on the promotion of Thai BL drama, considering the massive modification on the character, setting, plot, and language due to the creativity of AU authors. It is a unique finding that makes it possible to promote Thai BL actors. Finally, it will promote Thai BL drama which the actors are part of, which can be understood from the replies and quotes of X users as AU readers